Immunomodulatory properties of Bacillus subtilis extracellular vesicles on rainbow trout intestinal cells and splenic leukocytes - Vicente-Gil, Samuel; Nuñez-Ortiz, Noelia; Morel, Esther; Serra, Cláudia R.; Docando, Félix; Díaz-Rosales, Patricia; Tafalla, Carolina (Frontiers in Immunology, 2024)
Extracellular vesicles (EVs) are cell-derived membrane-surrounded vesicles that carry bioactive molecules. Among EVs, outer membrane vesicles (OMVs), specifically produced by Gram-negative bacteria, have been extensively characterized and their potential as vaccines, adjuvants or immunotherapeutic agents, broadly explored in mammals. Nonetheless, Gram-positive bacteria can also produce bilayered spherical structures from 20 to 400 nm involved in pathogenesis, antibiotic resistance, nutrient uptake and nucleic acid transfer. However, information regarding their immunomodulatory potential is very scarce, both in mammals and fish. In the current study, we have produced EVs from the Gram-positive probiotic Bacillus subtilis and evaluated their immunomodulatory capacities using a rainbow trout intestinal epithelial cell line (RTgutGC) and splenic leukocytes. B. subtilis EVs significantly up-regulated the transcription of several proinflammatory and antimicrobial genes in both RTgutGC cells and splenocytes, while also up-regulating many genes associated with B cell differentiation in the later. In concordance, B. subtilis EVs increased the number of IgM-secreting cells in splenocyte cultures, while at the same time increased the MHC II surface levels and antigen-processing capacities of splenic IgM + B cells. Interestingly, some of these experiments were repeated comparing the effects of B. subtilis EVs to EVs obtained from another Bacillus species, Bacillus megaterium, identifying important differences. The data presented provides evidence of the immunomodulatory capacities of Gram-positive EVs, pointing to the potential of B. subtilis EVs as adjuvants or immunostimulants for aquaculture.